Particles in wall-bounded turbulent flows : deposition, re-suspension and agglomeration - Minier, J. P.; Pozorski, J. (Springer, 2016)
The book presents an up-to-date review of turbulent two-phase flows with the dispersed phase, with an emphasis on the dynamics in the near-wall region. New insights to the flow physics are provided by direct numerical simuation and by fine experimental techniques. Also included are models of particle dynamics in wall-bounded turbulent flows, and a description of particle surface interactions including muti-layer deposition and re-suspension.
Keywords: Particles (Nuclear physics); Turbulence.; elektronické knihy; electronic books